Leptospirosis in Dairy Cattle from Southern Brazil - Risk Factors - Fadrique da Silva, Janaína; Hemb Alba, Diego Alexandre; Jorge, Sérgio; Gindri, Patrícia; Senna Bialves, Tatiane; Nunes de Souza, Guilherme; Pascoti Bruhn, Fábio Raphael; Cantarelli Pegoraro, Lígia Margareth; Dellagostin, Odir Antônio (Acta Scientiae Veterinariae, 2022)
Background: Cattle are susceptible to chronic leptospirosis infection, that results in reduced milk production and reproductive disorders such as abortions, stillbirths, fetal malformation, and mummified fetuses, causing significant economic losses. Commercially available vaccines against leptospirosis offer limited protection to cattle because they contain only the most prevalent serovars worldwide, even though they are not prevalent in the specific region. This study aimed to evaluate the prevalence of specific antibodies against Leptospira serogroups, reproductive disorders and the risk factors in dairy herds from different mesoregions of Rio Grande do Sul State, Southern Brazil. Materials, Methods & Results: An epidemiological survey was conducted, and serum samples from the bovine population representative of three mesoregions (MR1, MR2, and MR3) were studied; the samples were collected and tested for leptospirosis using the microscopic agglutination test (MAT) for 12 serogroups checking for the presence of agglutination. A total of 442 blood samples were collected from dairy cattle from November to December 2019 (MR1, 187; MR2, 88; and MR3, 167), including cows vaccinated with different commercial vaccines during the three months before sample collection (n = 295) and non-vaccinated against leptospirosis (n = 147). At the time of collection, an interview was conducted with the owners with questions about the health of the animals, management, habitat, feeding and reproduction. Chi-square tests univariate analysis with the SPSS® version 20.0 were performed to estimate the association of serogroup Djasiman seroreactivity with the occurrence of reproductive problems and related risk factors. The mean prevalence of antibodies against leptospires was 78.7% (MR1, 74.9 %; MR2, 84.1 %; and MR3, 80.2 %). Serogroup prevalence was different in each mesoregion evaluated and varied with vaccination status tested of the animals. The most prevalent serogroups in MR1 were Djasiman and Icterohaemorrhagiae. In MR2 and MR3, Djasiman was the most prevalent serogroup, regardless of vaccination status. Other prevalent serogroups in vaccinated animals were Icterohaemorrhagiae (MR1), Sejroe (MR2), Pomona, Sejroe, and Icterohaemorrhagiae (MR3). The other serovars tested had a prevalence of less or equal than 2%. The occurrence of reproductive problems with abortions and estrus repetition, was associated with reactivity to the serogroup Djasiman (P > 0.05). The results showed that the access of animals to flooded areas and the presence of rodents were significant risk factors, according to the literature. Discussion: The prevalence of antibodies against Leptospira in the studied areas was higher than expected, with a high prevalence of Djasiman serogroup. It is important to note that this serogroup is not present in current vaccine formulations. The presence of wetlands and rodents as risk factors in association with Djasiman is consistent with the scientific literature, since wild rodents are natural hosts, and swampy areas may allow Leptospira to survive for up to 180 days in the environment. Due to the presence and high prevalence found of the serogroup Djasiman in the experiment, new studies are being carried out to improve our knowledge about this serogroup and its possible inclusion in a commercial vaccine. Prophylaxis and control measures were recommended to rural producers in the analyzed properties. Keywords: bovine leptospirosis, herds, zoonosis, antibodies, reproductive disorders, leptospires, Djasiman.